Developing Tutorial Video Chassis Maintenance for Automotive Students at SMK Negeri 1 Seyegan - Dimas Kurniawan; Ibnu Siswanto (Universitas Sultan Ageng Tirtayasa, 2024)
The primary objective of this study is to develop tutorial videos addressing periodic maintenance procedures for light vehicle chassis at intervals of 5000, 10,000, 20,000, and 40,000 kilometers, while also assessing their suitability for educational purposes. The Research and Development (R&D) methodology, utilizing the ADDIE model, was employed for this purpose. The R&D process encompasses analysis, design, development, implementation, and evaluation stages. The study was conducted at SMK Negeri 1 Seyegan, where content and media experts served as respondents to evaluate the appropriateness of the tutorial videos. Additionally, 96 students from Class XI of the Automotive Light Vehicle Engineering department participated in trial sessions to assess the videos' usefulness. Data were gathered through interviews and questionnaires, followed by thorough analysis to elucidate the study's findings. The results revealed that the tutorial videos received very high ratings from content experts (96.5%) and favorable ratings from media experts (79.8%). Moreover, students, as potential users, gave the videos a high score of 80.43%. These findings indicate that the tutorial videos are well-suited for implementation in practical classroom activities.